Study of somatic, motor and functional effects of practicing initiation programs in water gymnastics and swimming by students of physical education and sports - Adela Badau (Physical Education of Students, 2017)
Introduction: The implementing within the academic physical education and sports curricula of a new discipline such as water gymnastics falls within the current trends of curriculum modernization. Purpose: The purpose of the study aims at evaluating the effects of driving, exercise-induced functional and somatic programs initiation of the gymnasts in the water compared to the effects specific to the initiation swimming. Material and Methods: research duration: two semesters / 14 practical courses. In the first semester the water gymnastics initiation program was implemented and in the second semester the swimming initiation program was implemented. Research Tests: Pretest in the first practical lesson of each semester and posttest in the last lesson of each semester. Participants: 34 male students, specializing in physical education and sport. Somatic, motor and functional assessment: weight, height, BMI, basal metabolism; H2O%, fat%, 2km UKK test, VO2max, fitness index. Statistical processing SPPS 20: arithmetic mean, standard deviation, t-test, probability threshold. Results: improvements relevant to the aqua-gymnastics group: VO2max 7.07 ml/min/kg; Test duration 2km UKK 1.049 minutes; BMI 0.255; and the group of swimming VO2max 0.43 ml/min/kg; Duration 2km UKK 0.44 minutes; BMI 0.139. Conclusions: effects on the functional motor and exercise-induced somatic programs initiation water gymnastics are significantly superior to those of initiation in swimming. We recommend conducting further studies to assess the effects of gymnastics on water through differentiated programs on levels of physical training, age, and the use of various sporting materials.